Methodology for Engineering Calculation of the Working Body for Continuous Fallow Field Tillage - S. I. Kambulov; V. B. Rykov; I. B. Bozhko; D. S. Podlesnyy (Сельскохозяйственные машины и технологии)
Tillage of fallow fields in summer is shown to be important for obtaining high quality food grains. The need for the engineering calculation of working bodies is emphasized, since the existing tillage machines and tools do not fully ensure the implementation of this technological process. (Research purpose) To develop a methodology for engineering calculation of the working body parameters for continuous fallow field tillage in summer. (Materials and methods) An analysis of the working body design has been conducted. It reveals that some of the working bodies bring a significant amount of wet soil layers to the surface, and others do not ensure a stable processing depth (4-6 centimeters) or do not completely destroy weeds. An engineering calculation method is proposed. It takes into account the following parameters of the working body: the angles of setting the lower part against the motion line and against the horizon, the angle of setting the upper part against the horizon, the conjugation radius of the upper and lower parts, the length of the cutting edge. (Results and discussion) A working body design is created meeting the agrotechnical requirements. The following parameters of the working body design are obtained: the angle of setting the lower part against the motion line is within 38-42 degrees and against the horizon – within 15-18 degrees, the angle of the upper part in the longitudinal-vertical and transverse-vertical planes is within 38-42 degrees, the conjugation radius of the upper and lower parts is within 0.2-0.3 millimeters, and the cutting edge length is of 282 millimeters. (Conclusions) A methodology for engineering calculation of the designed working body parameters is developed. It enables continuous fallow field tillage taking into account the soil physical and mechanical properties and the required indicators of the technological process.